HARMONISASI PEMIKIRAN SAINS DAN AGAMA DALAM PENDIDIKAN KARAKTER - Uyun, Nahdiyatul; Miftakhussurur , Muhammad; Hanif Mafudin, M. Mafkhan; Arfiani, Nina (Islamic Studies Journal for Social Transformation, 2024)
This study explores the relationship between science and religion in shaping the character of adolescents in the era of globalization. The main issue raised is the decline in moral values among youths as a result of the widespread influence of global culture and technological advancement. The objective is to analyze the integration between scientific rationality and religious spirituality in fostering moral integrity and responsible behavior among adolescents. The research method employs a qualitative approach by reviewing relevant literature and data from recent publications to examine moral and ethical trends influenced by globalized society. The findings show that globalization presents both challenges and opportunities, with exposure to foreign values often displacing local moral traditions. However, religion remains a stronghold of moral guidance, offering principles that can synergize with scientific thinking. A harmonious relationship between science and religion is crucial in reinforcing moral awareness and spiritual intelligence among youths. Teachers play a strategic role as educators and moral models in this integration process. The study concludes that an integrative curriculum and interdisciplinary research are effective strategies for aligning science and religion, especially in forming resilient and ethical youth. This harmonization is particularly significant for Generation Z, who face complex moral dilemmas in the digital age.